A question from kleppner's book

  • #1
MathematicalPhysicist
Gold Member
4,309
218
on page 108, question 2.34:
A mass m whirls around on a string which passes through a ring, ngelect gravity.
initially the mass is distance r0 from the centre and is revolving at angular velocity w0.
the string is pulled with constant velocity V starting at t=0 so that the radial distance to the mass decreases.
obtain a differential equation for w(t).

here what i did:
v'=w0r0
r(t)=r0+Vt
v'=w(t)*r(t)
w(t)r(t)=w0r0

but from the text this isnt correct, can someone help me here?
 

Answers and Replies

  • #2
34
0
1) Why the tangential velocity of the mass should be the same at any time?
2) You should to impose the angular momentum conservation law.
 
  • #3
MathematicalPhysicist
Gold Member
4,309
218
do you know a method which do not employ the angular momentum cl?
 
  • #4
34
0
If you cannot use angular momentum cl, thus you have to use cinematics.

Write the expressions for radial and tangential velocity (I mean the component which is orthogonal to the radial one) in polar coordinates and do the same for acceleration.
Take into account that it is a central motion (so acceleration only has the radial component).

Note that by saying that tangential acceleration is zero you are implicitly imposing the angular momentum conservation law.
 
Last edited:
  • #5
MathematicalPhysicist
Gold Member
4,309
218
here what i did so far:
v=dr/dtr+rdr/dt
a=d^2r/dt^2r+2w^2[tex]\theta[/tex]+r[tex]d\theta/dt[/tex][tex]\theta[/tex]-rw^2[tex]\theta[/tex]

now how do i proceed?
 
Last edited:
  • #6
34
0
loop quantum gravity said:
here what i did so far:
v=dr/dt<b>r<\b>+rd<b>r<\b>/dt
a=d^2r/dt^2<b>r<\bold>+2w^2[tex]<b>\theta<\b>[/tex]+r[tex]d\theta/dt[/tex][tex]<b>\theta<\b>[/tex]-rw^2[tex]<b>\theta<\b>[/tex]

now how do i proceed?
Well, begin by imposing that the radial component of the velocity is V and the tangential component of the acceleration is zero ...
 
  • #8
34
0
loop quantum gravity said:
you mean that:
dr/dt=V
and dr^2/dt^2=0?
I mean:

[tex]\frac{d \rho}{d t} = - V[/tex]

[tex]2 \frac{d \rho}{d t} \omega + \rho \frac{d \omega}{ dt} = 0[/tex].


You should be able to go on, now ...

EDIT: here [tex]\rho[/tex] is r.
 
Last edited:
  • #9
34
0
loop quantum gravity said:
here what i did so far:
v=dr/dtr+rdr/dt
a=d^2r/dt^2r+2w^2[tex]\theta[/tex]+r[tex]d\theta/dt[/tex][tex]\theta[/tex]-rw^2[tex]\theta[/tex]

now how do i proceed?
I think you didn't perform the correct derivation for the velocity and acceleration in polar coordinates ...
 
  • #10
MathematicalPhysicist
Gold Member
4,309
218
isnt v=d(rr)/dt
and a=dv/dt
?
according to these two equations i wrote the above.
 
  • #11
34
0
Velocity and acceleration in polar coordinates are:

[tex]v_r= \frac{d r}{d t}[/tex]

[tex]v_\theta = r \frac{d \theta}{d t}[/tex]

[tex]a_r = \frac{d^2 r}{d t^2} - r (\frac{d \theta}{d t})^2[/tex]

[tex]a_\theta = 2 \frac{d r}{d t} \frac{d \theta}{d t} + r \frac{d^2 \theta}{d t^2}[/tex]

with [tex] \omega = \frac{d \theta}{d t} [/tex].
 
  • #13
34
0
Ok. What's the problem then?
You have all you need to solve the question.
 
  • #14
MathematicalPhysicist
Gold Member
4,309
218
im having just one little problem, in the answer key it's written that:
if Vt=r0/2 then w=4w0.

while when i do the calculation:
[tex]\int_{0}^{t}2Vdt=\int_{w0}^{w(t)}\frac{dw}{w}[/tex]
which is:
2Vt=ln(w(t)/w0)
w(t)=(e^2Vt)*w0
which is clearly not the same as what is written in the answer key, can you point me where did i go wrong here?

thanks in advance.
 
  • #15
34
0
The integrand function on the left hand side of your equation is wrong ...

From the second equation in post n. 8 you get:

[tex]2 \int_{r_0}^r \frac{d \rho}{\rho} = - \int_{\omega_0}^{\omega} \frac{d \omega}{\omega} [/tex].
 
Last edited:
  • #16
MathematicalPhysicist
Gold Member
4,309
218
but from this equation we get:
2(ln(r-r0))=-ln(w-w0)
ln(r-r0)^2=ln(1/(w-w0))
(r-r0)2=1/(w-w0)
if i put r=Vt=r0/2 then i get
r0^2/4=1/(w-w0) and you havnet got rid from r0.
 
  • #17
34
0
loop quantum gravity said:
but from this equation we get:
2(ln(r-r0))=-ln(w-w0)
ln(r-r0)^2=ln(1/(w-w0))
(r-r0)2=1/(w-w0)
if i put r=Vt=r0/2 then i get
r0^2/4=1/(w-w0) and you havnet got rid from r0.
We don't get that! :cry:

I think you have some problems with the fundamental theorems of calculus or with logarithmic properties.

[tex]\ln r - \ln r_0 = \ln \frac{r}{r_0}[/tex]
[tex]\ln \omega - \ln \omega_0 = \ln \frac{\omega}{\omega_0}[/tex]
 
  • #18
MathematicalPhysicist
Gold Member
4,309
218
oh, my mistake. frogot to switch them.

i know these rules of logarithms, but i did a horribel mistake here.

nevermind, it's good to this now, before the exams. (-;
 
  • #19
MathematicalPhysicist
Gold Member
4,309
218
so idont need to use V here, or i shouldve used it here?
 
  • #21
34
0
loop quantum gravity said:
so idont need to use V here, or i shouldve used it here?
No, you don't. For the angular velocity, you only need initial position, initial w and final position.
 
Last edited:

Related Threads on A question from kleppner's book

Replies
2
Views
4K
Replies
1
Views
547
  • Last Post
Replies
4
Views
1K
Replies
0
Views
4K
  • Last Post
Replies
2
Views
4K
  • Last Post
Replies
11
Views
3K
  • Last Post
Replies
4
Views
1K
  • Last Post
Replies
5
Views
768
  • Last Post
Replies
17
Views
8K
  • Last Post
Replies
0
Views
5K
Top